Analisis Upaya Pengendalian Inflasi Era Covid-19 di Indonesia - Rahmat Putra Ahmad Hasibuan (Islamic Education Journal, 2022)
Analysis of Inflation Control Efforts in the Covid-19 Era in Indonesia. Indonesia as one of the countries affected by Covid is experiencing economic problems, namely high inflation rates and declining currency rates. This study aims to analyze efforts to control inflation both in terms of fiscal and monetary policies. This study uses descriptive qualitative methods sourced from secondary data from literature studies and scientific articles. The results of this study indicate that fiscal and monetary policies can control inflation by improving the real sector of the economy.